How has the US-China rivalry manifested in different legal regimes, such as the law of the sea, trade, and international institutions? - Li, Jianhao (Leo) (Technium Social Sciences Journal, 2026)
The US-China rivalry has altered the international legal regimes into hostility of strategic competition in 3 legal regimes. This paper will analyze how political and economic tensions manifest in the realms of international law that take advantage of ambiguities in the frameworks, particularly in associations such as the United Nations Convention on the Law of the Sea and the General Agreement on Tariffs and Trade. This paper discusses the comparison of past rivalries, particularly the US-Japan naval rivalries before WWII, as arguments are made regarding interpretations of China’s EEZ sovereignty claims of UNCLOS against the US interests of high seas freedoms, and US claims of security exceptions under GATT Article XXI against China’s retaliations to tariffs. The observational data indicates an increase of Freedom of Navigation Operations from 1-2 to 8-10 in 20 years, an investment decline from a peak of 13.8 billion to 8.7 billion in 4 years, and UNSC alignment drop from 90% to 60% and underscores a decline in bilateral values with the educational exchange dropping from 370,000 to under 300,000 in 5 years. This research finds the interconnectedness of the issues of spillover with economic losses and regular instances of GATT/FONOP issues. There are recommendations worth consideration to restore stability, including reviving the presidential US-China hotline, formally establishing a multilateral council specifically focused on UNCLOS/WTO reforms to resourceful responses to the challenges of transnational competition, and a Global Tech Exchange Initiative dedicated to stable bilateral relationship growth.